An exploration of psychosocial practice within private practice musculoskeletal physiotherapy: A cross-sectional survey. (October 2019) - Man, Isabella; Kumar, Saravana; Jones, Mark; Edwards, Ian
Abstract: Background: Patients with pain associated with musculoskeletal disorders often seek treatment from physiotherapists, necessitating these practitioners' competence to practice within the biopsychosocial framework. Qualitative research suggests musculoskeletal physiotherapists may not have adequate proficiency in psychosocial practice to assess and address psychosocial factors effectively. Objective: To collect quantitative self-report data via an online survey from a large cross section of Australian musculoskeletal physiotherapists regarding their psychosocial practice. Methods: The study involved an iterative survey development process followed by the conduct of this survey. A provisional survey named the 'Triple P Questionnaire' was developed, informed by the knowledge and experience of the research team. This Questionnaire was piloted by experts (n = 6) to provide feedback on the instrument. Changes were made to the survey based on this feedback. The finalised Triple P Questionnaire was distributed to Australian musculoskeletal physiotherapists. Results: 181 participants completed the full survey. Not all demographic characteristics were representative of the population. Most participants indicated that they 'agree' to most statements posed in the questionnaire including confidence, routine practice of specific psychosocial skills and barriers. Some questions presented a majority response of 'disagree' or a spread of responses, indicating some evidence-practice gaps, including the use of questionnaires, and explicit assessment of psychological factors. Inferential statistics revealed no significant correlations between demographic characteristics and psychosocial practice. Conclusion: The Triple P Questionnaire identified musculoskeletal physiotherapists' general confidence in their psychosocial practice but highlights some apparent inconsistencies in reported practice and areas where confidence is not as strong, reflecting possible evidence practice gaps. Highlights: Musculoskeletal physiotherapists report general confidence in psychosocial practice. They report less confidence using questionnaires and co-management of patients. A multitude of barriers to psychosocial practice were identified. Psychosocial professional development with practical application is indicated.